(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The experiment was conducted at Research and Development (R&D) farm of Ispahani Agro LTD., Rangpur in order to screen suitable carrot lines for commercial cultivation in Bangladesh. Two hybrid lines (02001 and 02002) and four open pollinated lines (01001, 01002, 01003 and 01004) were used in this screening program. The experiment was carried out following randomized complete block design with three replications. Results showed that root length and diameter of line 01004 were 14.66 and 3.580 cm, respectively. The standard weight of 5 roots was 519.3 g. Moreover, the line 01004 showed maximum quality roots and yield as compared to any other lines. This line is therefore can be recommended for commercial cultivation in Bangladesh. Res. Agric., Livest. Fish.2(1): 75-77, April 2015